The Relevance of Ibn Khaldun’s Educational Thought to the Implementation of Kurikulum Merdeka - Nurarifah, Lely (Universitas Islam Negeri (UIN) Mataram, 2024)
Kurikulum Merdeka emphasizes student-centered learning and grants teachers autonomy in selecting appropriate instructional methods. This study investigates the relevance of Ibn Khaldun’s educational methodology to the implementation of Kurikulum Merdeka. Utilizing a literature review approach, this research identifies several educational methods proposed by Ibn Khaldun, including memorization, discussion, rihlah (study-tour), gradual learning, repetition, and practical application. The findings indicate that these methods maintain significant relevance when applied to various components of the Kurikulum Merdeka in Indonesia. This research contributes to the ongoing dialogue between historical pedagogical approaches and contemporary curricular frameworks, offering insights into the enduring applicability of classical educational thought in modern educational contexts.